Underground innovation in mexican SME - Esparza-Rodíguez, Saúl Alfonso (2021)
Purpose: Small and Medium Enterprises (SMEs) are significantly relevant in the Mexican economy, employability, and innovation. In terms of understanding innovation on those companies that goes beyond formal innovation, the present work proposes to analyze “underground innovation”. Methodological design: Using the data available in the National Productivity and Entrepreneurial Competitive Survey for Mexican SME´s (ENAPROCE), we made a correlation analysis among organizational innovation, marketing innovation, process innovation, and product innovation to understand the relationship among different types of innovations which are usually related; then, a partial correlation test having the number of  registered industrial property (Brands, Patents, Utility Models, and Industrial designs) as a variable control to obtain the partial relation coefficient among variables related to informal non-registered innovation. The partial relationships among interactions related to stakeholders and underground innovation in Mexican SMEs are classified in three categories: positive (the person taking decisions; directive and supervision positions, external training, and participant in productive chains), negative (first-level supplier and commercial banks financing) and general (use of computers, higher education, and supplier of governments) partial relationships. Findings: The results show that the partial relationships among diverse stakeholders are significant to the innovation that is not registered nor acknowledged in Mexican SMEs, which is an indicator of a dynamic sector that responds to the needs and expectation of internal and internal factors in terms of the introduction of new products, processes, marketing and organizational changes, showing a better approach to understand the phenomena in small and medium business.